ANALYSIS OF MERGER OF PERUM PPD INTO PERUM DAMRI BASED ON REGULATIONS IN INDONESIA - Muthia Wulandari, Nadya; Azheri, Busyra; Adelina Mannas, Yussy (Universitas Ekasakti, 2023)
In Indonesia, SOE has a strategic role as a pioneer for business activities that cannot yet be carried out by the private sector, providing public benefits in the form of providing adequate goods and/or services to meet the needs of many people and actively providing assistance and guidance to the community. However, the challenges faced by SOEs are that there are too many SOEs, some SOEs have poor financial, operational and governance performance, and the roles and functions of SOEs themselves are still not efficient in supporting the national economy. Therefore, restructuring SOE has been carried out in an effort to streamline the number of SOEs in Indonesia, one of which is through a Merger. There are two road transport SOEs that currently play a role in the development and operation of national road transportation and have equivalent core businesses, namely Perum DAMRI and Perum PPD. Perum DAMRI and Perum PPD were both affected by the Covid-19 Pandemic so that both their financial and operational performance deteriorated. The Ministry of SOEs together with the Ministry of Finance initiated the merger of the two companies as a strategic effort to nourish the two companies. This study aims to analyze the legal aspects of the Merger of Perum PPD into Perum DAMRI. This research seeks to answer the following questions: what is the legal process for the merger of Perum DAMRI and Perum PPD based on regulations in force in Indonesia. The research method used is normative juridical. This study concludes that the merger of Perum with Perum has not been regulated directly in the existing laws and regulations in Indonesia. The merger of Perum PPD into Perum DAMRI currently still refers to regulations regarding the merger of SOE Companies. Several regulations related to the Merger of Public Corporations in Indonesia, especially regarding the Merger of Perum PPD into Perum DAMRI, including Law No. 19 of 2003 on SOE, GR No. 43 of 2005 concerning Mergers, Consolidations, Acquisitions, Changes in Legal Entity Forms of State-Owned Enterprises, Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, Law No. 13 of 2003 concerning Manpower as amended by Perppu No. 2/2022, Law no. 22 of 2009 concerning Road Traffic and Transportation as amended by Perppu No. 2/2022, and Government Regulation No. 30 of 2021 concerning Implementation of the Road Traffic and Transportation Sector.